RASSF1A controls tissue stiffness and cancer stem‐like cells in lung adenocarcinoma. (27th May 2019) - Pankova, Daniela; Jiang, Yanyan; Chatzifrangkeskou, Maria; Vendrell, Iolanda; Buzzelli, Jon; Ryan, Anderson; Brown, Cameron; O'Neill, Eric
Abstract: Lung cancer remains the leading cause of cancer‐related death due to poor treatment responses and resistance arising from tumour heterogeneity. Here, we show that adverse prognosis associated with epigenetic silencing of the tumour suppressor RASSF1A is due to increased deposition of extracellular matrix (ECM), tumour stiffness and metastatic dissemination in vitro and in vivo . We find that lung cancer cells with RASSF1A promoter methylation display constitutive nuclear YAP1 accumulation and expression of prolyl 4‐hydroxylase alpha‐2 (P4HA2) which increases collagen deposition. Furthermore, we identify that elevated collagen creates a stiff ECM which in turn triggers cancer stem‐like programming and metastatic dissemination in vivo . Re‐expression of RASSF1A or inhibition of P4HA2 activity reverses these effects and increases markers of lung differentiation (TTF‐1 and Mucin 5B). Our study identifies RASSF1A as a clinical biomarker associated with mechanical properties of ECM which increases the levels of cancer stemness and risk of metastatic progression in lung adenocarcinoma. Moreover, we highlight P4HA2 as a potential target for uncoupling ECM signals that support cancer stemness. Synopsis: The hippo signaling regulator RASSF1A is established as tumor suppressor in solid cancers, but the in vivo consequences of its loss have been difficult to discern. This study finds epigenetic suppression of RASSF1A in lung cancer to promote YAP‐dependent collagen deposition, leading to increased tumor stiffness, cancer stem‐cell reprograming, and risk of metastasis. RASSF1A suppresses metastatic dissemination in lung adenocarcinoma. Loss of RASSF1A leads to YAP‐dependent expression of collagen prolyl hydroxylase P4HA2 and elevated extracellular matrix (ECM) stiffness. ECM stiffness overrides RASSF1A‐mediated restriction of oncogenic YAP transcription. High stiffness triggers emergence of cancer stem‐like cells. Abstract : Epigenetic silencing of tumor suppressor RASSF1A promotes nuclear YAP1 accumulation and collagen deposition in the ECM.